Iraq's Marsh Arabs in the Garden of Eden - Ochsenschlager, Edward L. (Book collections on Project MUSE., 2004)
What can the present tell us about the past? From 1968 to 1990, Edward Ochsenschlager conducted ethnoarchaeological fieldwork near a mound called al-Hiba, in the marshes of southern Iraq. In examining the material culture of three tribes--their use of mud, reed, wood, and bitumen, and their husbandry of cattle, water buffalo, and sheep--he chronicles what is now a lost way of life. He helps us understand ancient manufacturing processes, an artifact's significance and the skill of those who create and use it, and the substantial moral authority wielded by village craftspeople. He reveals the complexities involved in the process of change, both natural and enforced. Al-Hiba contains the remains of Sumerian people who lived in the marshes more than 5,000 years ago in a similar ecological setting, using similar material resources. The archaeological evidence provides insights into everyday life in antiquity. Ochsenschlager enhances the comparisons of past and present by extensive illustrations from his fieldwork and also from the University Museum's rare archival photographs taken in the late nineteenth century by John Henry Haynes. This was long before Saddam Hussein drove one of the tribes from the marshes, forced the Bedouin to live elsewhere, and irrevocably changed the lives of those who tried to stay.